The role of asymptotic freedom for the pseudocritical temperature in magnetized quark matter - Farias, R. L. S.; Gomes, K. P.; Krein, G. [UNESP]; Pinto, M. B.; IOP (Iop Publishing Ltd, 2015)
Motivated by discrepancies observed between lattice QCD simulations and quark models regarding the behavior of the pseudo critical temperature for chiral symmetry restoration as a function of the magnetic field B, we investigate the effects of a running the quark coupling constant G with temperature T and the magnetic field B in the context of the Nambu-Jona-Lasinio model(NJL). Our point that when asymptotic freedom, an essential feature of QCD and absent in the model, is included through a running of G with T and B results from the NJL model can be brought in qualitative agreement with lattice QCD simulations.